Analysis of Modern Concepts of General Christian Education of Youth Value Orientations, as an Aspect of Professional Activity of Social Work - Serhiy Rabiichuk (Pedagogical Discourse, 2014)
The article is an analysis of modern concepts of general Christian education value orientations among young people, as an aspect of professional activity of social services. It is found out that young people today are actively involved in public life, without having their own views on the issue of values. In studying the problem of forming youth value orientations reveals the reasons and the conditions under which values are full of life benchmarks, personal priorities, and determine the nature of the study of personal life plans, actions and behavior of young people. It is argued that the formation of general Christian value orientations are ambiguous and problematic and is characterized by diversity goals, outcomes and areas of development. It is noted that most of the values are the foundation of morality, they jointly formed by external factors as well as the means and conditions for implementing intrinsic values – priority goals of the individual. The relevance of the concept of value consciousness is taken into account, which is no accident occurred at a time when the general Christian values require protection and preservation to transfer their legacy to future generations that should be in the process of future professionals of the social sphere. Accordingly, the system of value orientations is individual for each individual, in addition, it is closely related to the motives and needs, goals and attitudes, as well as the individual. It is taken into account that the efforts of the family, the entire educational educational system should aim at developing young general Christian values, in turn, acquired theoretical knowledge and practical experience with this problem is to promote effective professional activity of social services professionals.